Life Insurance as a Family Financial Protection Instrument: A Legal and Practical Study - Billy Prasetyo; Muhammad Jogi Uliando; Dhenis Indrawan; Andi Ghani Hasibuan; Nurleli Suseno (Jurnal Sahabat ISNU SU, 2026)
Family financial stability is highly vulnerable to unexpected risks, particularly the death of the primary income earner, which may significantly affect the welfare and economic sustainability of surviving family members. In this context, life insurance has become an important legal and financial instrument that not only provides economic protection but also establishes legal certainty through contractual arrangements between policyholders, insurers, and beneficiaries. This study aims to examine the role of life insurance as an instrument of family financial protection from both legal and practical perspectives by analyzing the legal position of the parties, the implementation of insurance claims, and the legal implications of life insurance for beneficiary families. This research employs a normative legal method using statutory and conceptual approaches. Legal materials were collected through library research, including legislation, legal doctrines, books, and scholarly journal articles concerning insurance law and family financial protection. The collected materials were analyzed qualitatively through legal interpretation and conceptual analysis. The findings reveal that life insurance performs a strategic function in maintaining family financial stability by transferring economic risk and providing legal protection through enforceable insurance agreements. Nevertheless, practical implementation continues to encounter several challenges, including limited legal literacy among policyholders, inadequate transparency regarding policy provisions, and disputes arising from insurance claim procedures. These issues potentially weaken legal certainty and reduce the effectiveness of life insurance as a family protection mechanism. The study concludes that the effectiveness of life insurance depends not only on comprehensive legal regulation but also on transparent contractual practices, good faith among contracting parties, effective regulatory supervision, and improved public legal awareness. Strengthening these aspects is essential to ensure that life insurance functions optimally as a sustainable instrument of family financial security and legal protection.